1994
DOI: 10.1111/j.1348-0421.1994.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Candida albicans Growth by Murine Peritoneal Neutrophils and Augmentation of the Inhibitory Activity by Bacterial Lipopolysaccharide and Cytokines

Abstract: Anti‐Candida activity of murine neutrophils and its regulation by immunomodulators were studied in vitro. Murine neutrophils which were prepared from peritoneal‐exudated cells inhibited the growth of Candida albicans at an effector: target (E/T) ratio of 30/1 or above. This anti‐Candida activity of neutrophils was augmented by lipopolysaccharide from Escherichia coli, murine tumor necrosis factor (TNF), murine interferon‐γ (IFN‐γ) and murine granulocyte macrophage colony‐stimulating factor (GM‐CSF) but not by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…A few studies have reported direct killing of yeasts by CD8 + T cells [58,59]. Alternatively IFN-c or TNF-a, produced by activated CD8 + T cells, could enhance anti-fungal activity of macrophages and neutrophils [60], since IFN-c is used as therapy for fungal infections [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have reported direct killing of yeasts by CD8 + T cells [58,59]. Alternatively IFN-c or TNF-a, produced by activated CD8 + T cells, could enhance anti-fungal activity of macrophages and neutrophils [60], since IFN-c is used as therapy for fungal infections [61].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported direct killing of yeasts by CD8 + T cells [58,59]. Alternatively IFN-c or TNF-a, produced by activated CD8 + T cells, could enhance anti-fungal activity of macrophages and neutrophils [60], since IFN-c is used as therapy for fungal infections [61].Previously, we have shown that CD8 -DC can crosspresent immune complexes [36]. In CD8 -DC this process is dependent on the signaling FcR c-chain, whereas cross-presentation by CD8 + DC does not require the FcR c-chain.…”
mentioning
confidence: 99%
“…It is well known that TNF-AE and IFN-ª stimulate macrophages and neutrophils, which kill C. albicans directly (Tansho et al, 1994). Farah et al (2002) demonstrated that TNF-AE in oral tissue was an important mediator in the recovery from oropharyngeal candidiasis in mice.…”
Section: Kinetics Of Numbers Of Pbl and Cln Cellsmentioning
confidence: 99%
“…This assay in microwell plates made possible accurate and objective measurement of Candida growth under the influence of a limited number of effector cells. In our experience with this assay technique, we noticed that 3H-glucose incorporation seemed to be correlated with the degree of hyphal growth of C. albicans which could be observed microscopically (5). We therefore wanted to develop a new nonradiolabel assay which rapidly and conventionally measured the effector cell inhibition of Candida growth.…”
mentioning
confidence: 99%